If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -6w = -10 Solving 10 + -6w = -10 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -6w = -10 + -10 Combine like terms: 10 + -10 = 0 0 + -6w = -10 + -10 -6w = -10 + -10 Combine like terms: -10 + -10 = -20 -6w = -20 Divide each side by '-6'. w = 3.333333333 Simplifying w = 3.333333333
| 3x-(2x+6)=2x-24 | | 8h=40 | | 2(-7v-8)=-86 | | 8B=-5+8B | | 2j=56 | | 25x+-45=180 | | 2(-2c-9)= | | 43=k-14 | | 3+2=-7 | | 7(5k+2)= | | 525+0.21d=585+0.13d | | 8x+3+4x=90 | | X^2-8x+12=24 | | -8(4m-9)= | | y^2=20-x^2 | | 8g-6g=8 | | 2x+1-x=-12 | | -w+173=3 | | 246=193-v | | 233-u=127 | | 49x^8+42x^4+9=f(x) | | 36-3w=w | | 7(6k-4)+3k=-388 | | 4x=5(3) | | 14x-16=124 | | 6v=4v+16 | | solvem-3.41=10.7 | | 4w=35-3w | | -4.1-9.12= | | 14u-49= | | 6(-8g+2)= | | -7v=-14 |